The missing P waves in wide QRS tachycardia - Mo, Jiangying; Jiang, Xuan; Zhang, Shuang; Li, Xuping; Chen, Mingxian (Frontiers in Physiology, 2026)
A 57-year-old male patient presented with paroxysmal palpitations for 2 years. The patient’s blood pressure was 120/76 mmHg; his heart rate was 149 beats/min. The presenting electrocardiogram showed a wide QRS complex tachycardia with an irregular rhythm. The RR intervals were irregular, and there were more complex QRS waves than P waves. The patient was first diagnosed with ventricular tachycardia. The ECG during sinus rhythm revealed a complete right bundle-branch block. The patient underwent an invasive electrophysiological study and was then diagnosed with atrioventricular nodal reentrant tachycardia (AVNRT). Following successful slow pathway radiofrequency ablation (located at the anterior part of the coronary sinus ostium), tachycardia was no longer inducible.